Karl Marx’s Eco-Socialism and Vision of Post-Capitalist Society - Edy Syahputra Sihombing; Jh Fandi Gilar Saputro; Yusuf Siswantara (Jurnal Ledalero, 2026)
Environmental degradation and climate change are serious global issues that threaten human life both today and in the future. In response to these crises, Kohei Saito seeks to investigate the idea of Marx’s eco socialism as a potential alternative. Marx’s ecological thinking is rooted in a critique of the capitalist mode of production, as the fundamental cause of environmental destruction. His criticism of capitalism centers on the idea of a "metabolic rift" between humans and nature. For Marx, the universal metabolism between humanity and the natural world takes place through the labour process. Through labour, humans strive to fulfil their needs by extracting natural materials. However, under capitalism, labour has been reengineered and monopolized solely to serve the purposes of increased production and the commodification of goods for profit. Kohei Saito undertakes a comprehensive investigation into Marx’s ecological ideas as a concrete response to environmental crises and the injustices rooted in capitalism. For Saito, the degradation of the environment can no longer be addressed merely through well-intentioned ecological attitudes or "green" ecological efforts that often conceal new forms of commodification and continue to uphold production processes even in the face of environmental decline. Through his reading of Marx’s ecological critique, Saito uncovers the vision of a post-capitalist society grounded in the concept of degrowth communism. Degrowth communism is Kohei Saito's interpretation of Karl Marx's ecological vision, namely a sustainable social order grounded in the principle of the metabolic relationship between human beings and nature. He argues that such a society represents a crucial and timely alternative one that is capable of responding meaningfully to the challenges of climate change and environmental degradation.